The quest for pluripotency: a comparative analysis across mammalian species. Issue 3 (September 2019) - Devika, A S; Wruck, Wasco; Adjaye, James; Sudheer, Smita
Abstract : Pluripotency is the developmental potential of a cell to give rise to all the cells in the three embryonic germ layers, including germline cells. Pluripotent stem cells (PSCs) can be embryonic, germ cell or somatic cell in origin and can adopt alternative states of pluripotency: naïve or primed. Although several reports have described the differentiation of PSCs to extra-embryonic lineages, such as primitive endoderm and trophectoderm, this is still debated among scientists in the field. In this review, we integrate the recent findings on pluripotency among mammals, alternative states of pluripotency, signalling pathways associated with maintaining pluripotency and the nature of PSCs derived from various mammals. PSCs from humans and mouse have been the most extensively studied. In other mammalian species, more research is required for understanding the optimum in vitro conditions required for either achieving pluripotency or preservation of distinct pluripotent states. A comparative high-throughput analysis of PSCs of genes expressed in naïve or primed states of humans, nonhuman primates (NHP) and rodents, based on publicly available datasets revealed the probable prominence of seven signalling pathways common among these species, irrespective of the states of pluripotency. We conclude by highlighting some of the unresolved questions and future directions of research on pluripotency in mammals.